Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Microstructural reorganization and cargo release in pyrene urethane methacrylate random copolymer hollow capsules - Kaushlendra, K.; Asha, S. K. (Langmuir, 2012)
We report the synthesis of polymer microcapsules by direct one-pot free radical random copolymerization approach. Urethane methacrylate comb monomers having pendant pyrene (Py) and 3-pentadecyl phenol (PDP) units were copolymerized in a random manner using benzoyl peroxide (BPO) as free radical initiator in dimethylformamide (DMF) as solvent. These copolymers and corresponding homopolymers spontaneously self-organized into microspheres upon drop casting from solvents like DMF and tetrahydrofuran (THF). Stable microspheres were obtained in water by dialyzing THF solution of the polymers against water in dialysis bags with molecular weight cutoff of similar to 2000. The hollow nature of the spheres was confirmed by rhodamine B (RhB) encapsulation followed by Forster resonance energy transfer (FRET) based fluorescence emission from RhB upon exciting pyrene. The microenvironment inside the capsule was probed by following the I-1/I-3 ratio of pyrene emission as well as RhB release as a function of temperature. The RhB encapsulated in the pyrene homopolymer PIHP-100Py capsules experienced strong donor-acceptor interaction and did not undergo complete release even at high temperature (85 degrees C). The encapsulated RhB from the copolymers with low pyrene incorporation was released almost fully upon heating beyond 50 degrees C. Pyrene moieties in the PIHP-100Py were shielded from surrounding water and experienced a hydrophobic environment, whereas in the low pyrene incorporated copolymer the PDP units were better shielded from the hydrophilic environment. This work represents a simple approach to produce polymer hollow capsules, and the varying pyrene incorporation was used to trace the microenvironment inside the capsules.

Variable-temperature time-resolved emission spectra studies of random pyrene urethane methacrylate copolymers with high pyrene incorporation - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2013)
A series of random co-polyurethane methacrylate comb polymers with pyrene (Py) and 3-pentadecylphenol (PDP) as pendant units Were prepared by free radical polymerization. The pyrene labeling was varied from 1 to 100 mol %. The excimer emission of these copolymers were studied as a function of both time and temperature using time-resolved emission spectra (TRES) experiments and variable-temperature steady-state fluorescence measurements. Variable-temperature steady-state as well as decay experiments showed that the contribution from excimers via diffusional encounters increased at the cost of pyrene monomer as the temperature increased until similar to 50 degrees C; beyond which nonradiative losses predominated. TRES collected at 25 and 70 degrees C were compared to study the nature and origin of emitting species as a function of pyrene loading. TRES at 25 degrees C dearly indicated the presence of ground state pyrene dimers with emission centered at similar to 435 nm which soon gave way to emission centered around 465 and 485 nm in the time gated spectra collected at higher time intervals. In TRES collected at 70 degrees C, excimer emission centered at 465 and 485 nm was very high even at short time scales. The lowest pyrene loaded polymer PIHPDP-1Py did not exhibit excimer emission in the TRES collected at 25 degrees C as well as 70 degrees C.

H-bonding vs non-h bonding in 100% pyrene methacrylate comb polymers:self assembly probed by tres and temperature dependent fluorescence - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
The differences in self-organization behavior in novel 100% pyrene labeled comb methacrylate polymers probed as a function of their varied origins of excimer formation are presented. The different structural variations in the polymers included the presence or absence of hydrogen bonding interactions in the form of urethane linkages, short or long alkyl spacer segments separating the pyrene units from the polymer backbone and linear versus kinked urethane linkage. The effect of variable concentration and temperature on the chemical shift of the NH proton of the urethane linkage was probed using 1H NMR experiments conducted at temperatures varying from 25 to 70 °C at two different concentrations (2.5 and 25 mmol) in DMSO-d6 as solvent. The photophysical properties of the polymers in dilute DMF solutions were investigated by steady state emission, fluorescence decay studies, time-resolved emission spectra (TRES), and variable temperature emission studies. It was observed that the polymer poly(PBH) having a non-hydrogen-bondable ester linkage in the pendant chains formed an excimer completely via a static mechanism and the ground state aggregate species were not broken even at higher temperatures. The polymer poly(PIC) having a short hydrogen-bondable urethane linkage formed an excimer via a static as well as dynamic mechanism. The other hydrogen-bondable urethane methacrylate polymers having a linear linker poly(PHH) and kinked linker (PIHP) formed excimer mostly via a dynamic mechanism with a very small contribution from the static route. The TRES studies carried out for the polymers provided significant insight into the excimer formation mechanism in these polymers. The variable temperature fluorescence studies highlighted the differences in the H-bonded vs non-H-bonded polymer as a function of their excimer recovery upon cooling.